Survival of Ice Nucleation-Active and Genetically Engineered Non-Ice-Nucleating Pseudomonas syringae Strains after Freezing - Buttner, Mark P. (1989)
The survival after freezing of ice nucleation-active (INA) and genetically engineered non-INA strains of Pseudomonas syringae was compared. Each strain was applied to oat seedlings and allowed to colonize for 3 days, and the plants were subjected to various freezing temperatures. Plant leaves were harvested before and after freezing on two consecutive days, and bacterial populations were determined. Populations of the INA wild-type strain increased 15-fold in the 18 h after the oat plants incurred frost damage at −5 and −12°C. Plants colonized by the non-INA strain were undamaged at −5°C and exhibited no changes in population size after two freeze trials. As freezing temperatures were lowered (−7, −9, and −12°C), oat plants colonized by the non-INA strain suffered increased frost damage concomitant with bacterial population increases following 18 h. At −12°C, both strains behaved identically. The data show a relationship between frost damage to plants and increased bacterial population size during the following 18 h, indicating a potential competitive advantage of INA strains of P. syringae over non-INA strains in mild freezing environments.